2016
DOI: 10.1590/bjpt-rbf.2014.0161
|View full text |Cite
|
Sign up to set email alerts
|

Delayed effect of Kinesio Taping on neuromuscular performance, balance, and lower limb function in healthy individuals: a randomized controlled trial

Abstract: BackgroundKinesio Taping (KT) is an elastic bandage that aims to improve neuromuscular performance, although there is no consensus as to its benefits.ObjectiveTo analyze the immediate and delayed effects of KT on the neuromuscular performance of the femoral quadriceps, on balance, and lower limb function in healthy subjects.MethodThis is a randomized controlled trial. Thirty-six women with a mean age of 22.2±3.6 years and BMI of 22.5±2.3 Kg/m2 were divided into three groups: control, with ten minutes of rest (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 19 publications
3
15
1
Order By: Relevance
“…With respect to EMG activity, even though the theories indicated that KT can activate skin receptors and improve neuromuscular recruitment, our study revealed no significant taping or time differences. VMO and VL activity did not change after taping for 0.5 or 1 h. The finding partly supports the results of previous studies where no significant difference was observed after taping 24 or 48 h (Lins et al, 2016). This study also supported other recent studies indicating that the stimulation of KT cannot activate quadricep activity (Lins et al, 2013;Oliveira et al, 2016;Serrao et al, 2016;Melo et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…With respect to EMG activity, even though the theories indicated that KT can activate skin receptors and improve neuromuscular recruitment, our study revealed no significant taping or time differences. VMO and VL activity did not change after taping for 0.5 or 1 h. The finding partly supports the results of previous studies where no significant difference was observed after taping 24 or 48 h (Lins et al, 2016). This study also supported other recent studies indicating that the stimulation of KT cannot activate quadricep activity (Lins et al, 2013;Oliveira et al, 2016;Serrao et al, 2016;Melo et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…These findings are similar to those in the study (26) conducted to verify the immediate and late effects on the femoral quadriceps, on balance and lower limb function in 36 healthy women. Those women were randomly divided into three groups: control (with a 10-minute rest), one group wearing the elastic therapeutic tape applied with no tension on the quadriceps and the other group wearing the elastic therapeutic tape applied with tension on the same muscle.…”
Section: Discussionsupporting
confidence: 89%
“…Creating a group who had the elastic therapeutic tape applied with no tension (in this case, G2) was justified by the hypothesis that only stimuli in the integumentary system would already be enough to stimulate the somatosensory receptors inserted in the skin and thus produce motor responses (2) . According to certain authors (5,26) , integumentary stimulation by applying tension-free elastic therapeutic tape may be considered a kind of placebo.…”
Section: Discussionmentioning
confidence: 99%
“…According to the recent literature, there are many studies relating to Kinesio Taping, muscle strength and ROM. 12,21---27 In relation to strength, three studies 12,21,22 compared the effects of Kinesio Taping on quadriceps strength in health subjects and did not find any improvements when compared to a control group (no taping) and placebo group (KT without tension). Similarly, two studies 23,24 did not find any improvements on quadriceps strength in soccer players when compared KT to placebo taping (KT without tension and micropore).…”
Section: Discussionmentioning
confidence: 99%